Evaluation of improved clusterbean varieties for growth, yield and economies south-west region of Punjab. - Manhas, S.S.; Singh, Harpreet (Annals of Agricultural Research, 2019)
A field experiment was carried out at Bathinda during kharif- 2012 to evaluate improved clusterbean varieties for growth and yield under semiarid irrigated conditions of south-west region of Punjab. Clusterbean cultivated in south-west region of Punjab showed a very good adaptation. Significant differences between varieties were found for plant height, branch number, days to maturity and seed yield. The maximum plant height was observed with AG 112 and RGC 197 respectively which was significant more than RGC 1066, RGC 936, RGC 1055, HG 2-20, RGC 1031, RGC 1017, RGC 1003, HG 365 and RGC 1002 while at par to G 80. Variety RGC 1031 resulted maximum no. of branches which was at par with G 80 and RGC 936 while significantly more than other varieties of clusterbean. The significantly less no. of days to maturity were observed with RGC 1017 which were at par to RGC 936, RGC 1055, HG 2-20, and HG 367 and significantly lower than other varieties. The maximum numbers of pods were observed with HG 2-20 which were at par with HG 365 and significant higher than other varieties. The numbers of grains per pod and 100-seed weight were non-significantly affected by different clusterbean varieties. The maximum yield was observed with HG 2-20 (1576.5 kg/ha) which was at par with HG-365 and RGC-936 and significantly higher than other varieties. The maximum dry fodder yield was recorded with RGC 1031 (3313.7 kg/ha) which was followed by G 80 (2805.5 kg/ha) and significantly higher than other varieties of clusterbean.